1991
DOI: 10.1111/j.1469-8137.1991.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some triazole fungicides on intracellular pH and on cell membrane permeability in leaves of Elodea densa (Planch.) Casp.*

Abstract: SUMMARYRecent data obtained in this laboratory have shown that a number of triazole fungicides induce in leaves of barley and Elodea densa an early release of solutes and an inhibition of H* extrusion. This paper deals with the early effects of two triazoles, penconazole and flusilazol, on intracellular pH and plasmamembrane permeability in Elodea densa leaves.Different effects were found at low (0-1-0-15 mM) or at high (O-3-O-5 mivi) triazole concentrations. At the low concentrations the triazoles induced a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This parameter, according to the biochemical pH-stat theory of Davies (1973), should reflect the changes in the rate of synthesis or decarboxylation of malate, due to cytosolic alkalinization or acidification, respectively. The results of experiments carried out in the presence of KCl or FC plus KCl, indicated that while FC markedly increased COj fixation, as already shown in other materials (Johnson and Rayle, 1976;Romani et al 1983), ABA induced a clear inhibition of CO2 fixation rate in both cases (Fig. 4).…”
Section: Effects Of Fusicoccin and Of Abscisic Acid On Dark Coj Fixationsupporting
confidence: 81%
See 2 more Smart Citations
“…This parameter, according to the biochemical pH-stat theory of Davies (1973), should reflect the changes in the rate of synthesis or decarboxylation of malate, due to cytosolic alkalinization or acidification, respectively. The results of experiments carried out in the presence of KCl or FC plus KCl, indicated that while FC markedly increased COj fixation, as already shown in other materials (Johnson and Rayle, 1976;Romani et al 1983), ABA induced a clear inhibition of CO2 fixation rate in both cases (Fig. 4).…”
Section: Effects Of Fusicoccin and Of Abscisic Acid On Dark Coj Fixationsupporting
confidence: 81%
“…Thus, neither a decrease in H* apparent net influx oor an increase in cell sap pH should be found in these conditions, unless an overstimulation of the proton pump, possibly by acid load, had been induced (for similar effects in other materials see Romani et al 1985, Reid et ai. 1989, Beffagna and Romani 1991.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radioactivity incorporated was always measured by liquid scintillation counting, after digestion and bleaching of the tissue, as described in a previous paper (Romani and Beffagna, 1991 [35] ), and determined by a Packard TriCarb counter after addition of 10 ml scintillation liquid (Hionic Fluor, Packard).…”
Section: Ca 2+ Efflux Experimentsmentioning
confidence: 99%
“…The present work deals with the results of some experiments aimed at characterizing in vivo both features of the Ca 2+ fluxes and the significance of the Ca 2+ pump-mediated H + /Ca 2+ exchanges at plasmalemma level in Egeria densa leaves. This material is particularly suitable for in vivo transport studies and accurate pH cyt measurements, and has been extensively characterized in the past in our laboratory (Marrè et al, 1987 [26] ; Beffagna and Romani, 1988 [3] , 1989 [4] , 1991 [5] ; Marrè et al, 1989 [27] ; Romani and Beffagna, 1991 [35] ; Beffagna et al, 1995 [6] ; Meraviglia et al, 1996 [28] ). Some results, aimed at a better understanding of the sequence of events occurring in adult tissues under ABA treatment, are also presented, suggesting the possible involvement of Ca 2+ -ATPase activity in inducing the -∆H + decrease and early cytoplasmic acidification, previously detected in the presence of ABA, either in leaves of barley and Elodea densa or in Arabidopsis thaliana seedlings (Beffagna, 1992 [2] , Beffagna et al, 1995 [6] , 1997 [7] ).…”
Section: Introductionmentioning
confidence: 99%